2016
DOI: 10.1039/c6sc01295g
|View full text |Cite
|
Sign up to set email alerts
|

Establishing hierarchy: the chain of events leading to the formation of silicalite-1 nanosheets

Abstract: In applying a multi-scale spectroscopic and computational approach, we demonstrate that the synthesis of stacked zeolite silicalite-1 nanosheets, in the presence of a long-tail diquaternary ammonium salt surfactant, proceeds through a pre-organised phase in the condensed state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…To prevent the metal aggregation, the introduction of a mesoporous system into the microporous zeolite network can greatly improve the dispersion of metal species due to a large increasing number of defect sites [33]. With the benefits of mesoporous or hierarchical structures [34,35], an improved catalytic efficiency has been observed in some reactions, in particular the processes involving bulky molecules, such as hydroisomerization, aromatization and hydrodesulfurization, as compared to a conventional zeolite [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent the metal aggregation, the introduction of a mesoporous system into the microporous zeolite network can greatly improve the dispersion of metal species due to a large increasing number of defect sites [33]. With the benefits of mesoporous or hierarchical structures [34,35], an improved catalytic efficiency has been observed in some reactions, in particular the processes involving bulky molecules, such as hydroisomerization, aromatization and hydrodesulfurization, as compared to a conventional zeolite [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of the quasi-Bragg peak, around q = 1.6 nm −1 , is typical for an assembly of stacked sheets-a paracrystalline system. [26] The line shape of the quasi Bragg peak, deviates from a Gaussian profile. It is broad, and sharpens toward the top.…”
mentioning
confidence: 99%
“… 151 , 152 The possibility to rationally design the amphiphilic mesoporogens was recently outlined by Zhu et al, who studied the early stages of MFI nanosheet synthesis by operando small-angle X-ray scattering, complementary characterization techniques, and molecular modeling. 153 The authors found that the meso-order is established at the very beginning of synthesis and that amphiphilic SDA stabilizes pre-zeolitic species via a molecular-recognition-type mechanism, followed by the micro-ordering into zeolite nanosheets. It was also shown that the rational fine-tuning of the ammonium headgroup allows synthesis of different zeolite topologies (namely, MFI and MEL) and aspect ratios (nanosheets or needles).…”
Section: Engineering Well-defined Zeolite Catalystsmentioning
confidence: 99%